A Profile of Language Errors in Preschool Typically Developing Children and Children With Developmental Language Disorder - Balčiūnienė, Ingrida; Kamandulytė-Merfeldienė, Laura (Pedagogika, 2025)
The study aimed at exploring both qualitative and quantitative aspects of language errors in Lithuanian children aged 5 to 6 with developmental language disorder (DLD) compared to their typically developing peers. Overall, 160 children participated in the assessment. Half of them were clinically identified with DLD, forming the experimental group, while the remaining half, consisting of typically developing children, served as the control group. Each child was individually assessed through two methods: 1) storytelling according to picture sequence and 2) reasoning dialogue. The qualitative analysis of the collected data revealed that children across both groups exhibited language errors of a similar typological nature, yet the frequency and distribution of these error types and subtypes varied between the groups. Quantitative analysis identified several statistically meaningful variables that could serve to distinguish between children with typical development and those with DLD. The implications of these findings suggest that while the typology of language errors remains consistent across developmentally diverse groups, the underlying mechanisms and severity of these errors differ substantially. In addition, understanding the specific language error patterns in children with DLD could suggest targeted language intervention strategies.